Justice and the rule of law ; And now, the bad news ; Awit ni Pulau [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Interview with Col. Bobby Ortega, Baguio City chief of police about armies, criminals, and extra judicial execution. Takes a look at exporter entrepreneurs. The story of Pulau shown on stage. Interview with Ed Maranan, a children stories' writer and the author of "Awit ni Pulau", an ecological parable.